2021
DOI: 10.1039/d1ra00816a
|View full text |Cite
|
Sign up to set email alerts
|

High pressure polymorphism of LiBH4 and of NaBH4

Abstract: Diamond anvil cell experiments are used along with density functional theory calculations to extend the phase diagram of LiBH4 & NaBH4 and explore new NaBH4(H2)x compounds at Mbar pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…The XRD peaks of NaBH 4 are shifted at increasing pressure, indicating a change in the crystal structure or crystallite size, which may be due to the NaBH 4 phase transition. The phase transitions can create new crystallographic phases (α to β phase), changing the XRD pattern and peak intensities. ,,, Similarly, in Figure b, the phase intensity of the composite material (30CaCl 2 /NaBH 4 ) gradually decreased as the system pressure was increased and the decomposition rate was more at a low pressure compared to a high pressure and shifted to higher 2θ values [Δ­(2θ) ∼ 0.25°]. The peak intensity decreased, and hydrogen generation was low at a high pressure (20 bar).…”
Section: Synthesized Materials Characterizationmentioning
confidence: 91%
See 1 more Smart Citation
“…The XRD peaks of NaBH 4 are shifted at increasing pressure, indicating a change in the crystal structure or crystallite size, which may be due to the NaBH 4 phase transition. The phase transitions can create new crystallographic phases (α to β phase), changing the XRD pattern and peak intensities. ,,, Similarly, in Figure b, the phase intensity of the composite material (30CaCl 2 /NaBH 4 ) gradually decreased as the system pressure was increased and the decomposition rate was more at a low pressure compared to a high pressure and shifted to higher 2θ values [Δ­(2θ) ∼ 0.25°]. The peak intensity decreased, and hydrogen generation was low at a high pressure (20 bar).…”
Section: Synthesized Materials Characterizationmentioning
confidence: 91%
“…Moreover, the decrease of the peak intensity was comparatively lower with 30CaCl 2 /NaBH 4 than pure NaBH 4 (the changes are shown in the inset of the figure). 43,46,50 The study suggested that the composite material 30CaCl 2 /NaBH 4 was more stable at a high pressure (20 bar) than pure NaBH 4 . Thus, the study was consistent and suggested that the crystalline phase of NaBH 4 gradually decreased with increasing system pressure.…”
Section: Raman Spectral Analysismentioning
confidence: 99%
“…Of particular interest in this respect, are the various complexes with H 2 and pressure-induced phase transitions of ammonia borane [134][135][136][137] and its derivatives, 138 alanates, 139 metal amides 140 and borohydrides. 137,141,142 The majority of these systems were thoroughly explored by means of HP-Raman spectroscopy, but for sure, employment of IR spectroscopy would add very interesting information of high importance for their utilisation. In a recent publication, Marizy et al reported a HP-IR study of polymorphism of LiBH 4 and NaBH 4 .…”
Section: Mechanicsmentioning
confidence: 99%
“…In a recent publication, Marizy et al reported a HP-IR study of polymorphism of LiBH 4 and NaBH 4 . 142 The authors pointed out that it is impossible to determine the details of the phase transition of NaBH 4 from tetragonal Pnma to α-LiBH 4 -type monoclinic P 2 1 / c using Raman spectroscopy, 141 claiming that “it is not possible to confirm the phase transition above 20 GPa from the Raman spectra alone”. Thus, they performed HP-IR measurements up to 200 GPa.…”
Section: Physical Processesmentioning
confidence: 99%